New species and new collection records of aquatic beetles in the genus Ochthebius Leach from southern Africa (Coleoptera: Hydraenidae) - Perkins, Philip D. (Zootaxa, 2011)
The southern African species of the water beetle genus Ochthebius Leach, 1815, are reviewed. Eight new species are described, and new collection records are given for eight previously described species, based on the examination and databasing of 8,919 specimens from 253 localities/events. Male genitalia of the new species are illustrated, and high resolution habitus images of the holotypes of new species are provided. Distribution maps are given for the 18 species of Ochthebius now known from southern Africa, including Namibia, South Africa, Lesotho, Zimbabwe, the extreme southern part of Angola, and the southern part of Mozambique. New species of Ochthebius are: O. anchorus (South Africa, KwaZulu-Natal Province, Oribi Gorge); O. bicomicus (South Africa, Western Cape Province, 22 mi. N. Nelspoort); O. bupunctus (Namibia, Kaokoveld, Kunene River, Swartbooisdrift); O. endroedyi (South Africa, North West Province, Barberspan); O. granulinus (South Africa, Western Cape Province, Elandsdrift); O. involatus (South Africa, Western Cape Province, near Kommetje); O. sitiensis (Namibia, Okau Fountain, 12.5 km inland); and O. zulu (South Africa, KwaZulu-Natal Province, Nqutu).